Respuesta :

Step-by-step explanation:

Step 1:  Multiply both sides by x

[tex]\frac{8x-3}{x}*x = 2*x[/tex]

[tex]8x-3=2x[/tex]

Step 2:  Subtract 2x from both sides

[tex]8x-2x - 3 = 2x - 2x[/tex]

[tex]6x - 3 = 0[/tex]

Step 3:  Add 3 to both sides

[tex]6x-3+3=0+3[/tex]

[tex]6x=3[/tex]

Step 4:  Divide both sides by 6

[tex]6x/6=3/6[/tex]

[tex]x=\frac{1}{2}[/tex]

Answer:  [tex]x=\frac{1}{2}[/tex]

Answer:

x = ½

Step-by-step explanation:

(8x - 3)/x = 2

8x - 3 = 2x

6x = 3

x =3/6

x = 1/2